PENGARUH PENGALAMAN KERJA, DUE PROFESSIONAL CARE, TIME BUDGET PRESSURE, LOCUS OF CONTROL TERHADAP KUALITAS HASIL KERJA AUDITOR - Mareta Rahmadya Iskandar, (2021)
The Influence of Work Experience, Due Professional Care, Time Budget Pressure, Locus of Control on Auditors Quality of Work By Mareta Rahmadya Iskandar Abstract This research was conducted to examine the effect of work experience of each external government auditor, due professional care, time budget pressure and locus of control on the auditor quality of work. The population of this research is an external governments auditor that works in BPK RI representative of West Sumatera Province. All of the population in this research are the samples. This study analyzes the questionnaire from primary data derived from respondents' answers as many as 45 auditors. The analysis technique used is Structural Equation Modeling (SEM) using the application Smart Partial Least Square version 3.0 with an error rate of 5%. The results of the study indicate that Work Experience, Due Professional Care, Time Budget Pressure has a significant effect on the Auditor Quality of Work and Locus of Control does not significantly influence the Auditor Quality of Work. Keywords: Work Experience (PK), Due Professional Care (DPC), Time Budget Pressure (TBP), Locus of Control (LOC) and Auditors Quality of Work (KHKA)